Design Thinking-Based Development of a Holistic Application for Efficient Lecture Hall Management in Music Education - Nanang Supriatna; Agus Firmansah; Andrian Purwanto (Didaktika: Jurnal Kependidikan, 2025)
The objective of this research is to create and evaluate a holistic application prototype for lecture room management in the UPI Music Arts Study Program. This method will use a design thinking approach. Among the challenges that arise in effective and efficient lecture room management are scheduling conflicts, rapid changes in room needs, and a lack of real-time data. Automatic scheduling, real-time room booking, and accurate usage reporting are some of the features offered by the developed application. Empathy, definition, ideation, prototyping, and testing are the steps in the design thinking process used. To obtain direct feedback, students and instructors used the prototype for testing. The results of the study indicate that this application successfully increased user satisfaction, reduced scheduling errors, and improved the effectiveness and efficiency of lecture room management. By using performance evaluation, managers can better track room usage and make better decisions about resource allocation. This research emphasizes the importance of technological innovation in higher education management and provides a foundation for other institutions to adopt it. Additional recommendations include evaluating the long-term impact on academic performance and user satisfaction, using real-time notifications, enhancing data security, and integrating with other academic systems. By addressing these recommendations, institutions can further improve their room management processes, ensuring optimal use of space and resources. The holistic approach and technological integration proposed in this research offer a sustainable solution for managing educational facilities efficiently and effectively, catering to the dynamic needs of both students and faculty.